AN ANALYSIS OF SPEECH ERRORS ON THE TEDX TALKS YOUTUBE CHANNEL - Pratiwi, Nur Ulfa; Faradiba, Syarifah; Tahir, Muh. (JTechLP: Journal of Technology in Language Pedagogy, 2022)
The purpose of this research was to describe how often each type of speech error was and the types of speech errors that showed up in TEDx Talks. This study uses a qualitative method. The researchers chose 15 public speakers on TEDx Talks. The sample was selected using purposive sampling. The research instrument is video documentation. The result of the data analysis found, there was found that there are of the 15 videos from TEDx Talks YouTube Channel, there are 3 videos that often do silent pauses, 10 videos that often do fill a pause, there are 10 videos that often repeat, there are 5 videos that often retraced false start, there are 6 videos that often do unretraced false start, there are 3 videos that do corrections, there are 5 videos that often do interjections, there are 2 videos that often do stutters, and there is 1 video that often doses the slip of the tongue. The types of speech errors found in this research based on Clark and Clark’s 1977 theory from the 15 TEDx Talks YouTube Channel videos there are silent pause, filled pause, repeat, retraced false start, unretraced false start, corrections, interjections, stutters, and slip of the tongue.